2008
DOI: 10.1016/j.ophtha.2007.04.049
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Mellitus and the Risk of Open-angle Glaucoma

Abstract: Purpose-To examine the relationship between type 2 diabetes mellitus (T2DM) and the risk of having open-angle glaucoma (OAG) in an adult Latino population. Design-Population-based cross-sectional study.Participants-Latinos 40 years and older (n = 5894) from 6 census tracts in Los Angeles, California. Methods-Participants from the Los Angeles Latino Eye Study (LALES), a large populationbased study of self-identified adult Latinos, answered an interviewer-administered questionnaire and underwent a clinical and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
117
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(127 citation statements)
references
References 22 publications
6
117
1
3
Order By: Relevance
“…18,20 Bonovas and colleagues conducted a metaanalysis examining the relationship between diabetes and primary OAG (POAG). They reviewed a total of 12 studies published between 1987 and 2001, which included 5 casecontrol and 7 cross-sectional studies.…”
Section: Studies Relating Glaucoma and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…18,20 Bonovas and colleagues conducted a metaanalysis examining the relationship between diabetes and primary OAG (POAG). They reviewed a total of 12 studies published between 1987 and 2001, which included 5 casecontrol and 7 cross-sectional studies.…”
Section: Studies Relating Glaucoma and Diabetesmentioning
confidence: 99%
“…[15][16][17] Likewise, vascular dysregulation has been well documented in diabetic patients and has been hypothesized to cause downstream microvascular consequences, including retinopathy and neuropathy. 18,19 As vascular abnormalities are associated with both diseases and these deficits may predispose patients toward a comorbid state, further evaluation to determine whether OAG patients with diabetes are more prone to glaucomatous progression is essential.…”
mentioning
confidence: 99%
“…In literature, studies gave various outcomes regarding the relationship between glaucoma and diabetes. Some studies have confirmed a significant relationship between diabetes and glaucoma which implies metformin use and dose [8][9] . On the other hand, other studies did not confirm such a relationship [10][11] .…”
Section: Discussionmentioning
confidence: 98%
“…The relationship between DM and glaucoma was investigated through several studies; some studies reported significant relationship [8][9] . Other studies did not report a significant relationship between DM and glaucoma [10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is considered an important risk factor for primary open-angle glaucoma [1]. Moreover, diabetic retinopathy often coexists with glaucomatous optic neuropathy.…”
Section: Introductionmentioning
confidence: 99%